OS 15-03 A NOVEL MECHANISM FOR ALDOSTERONE PRODUCTION THROUGH BETA 3 ADRENERGIC RECEPTOR (β3-AR) IN HEART FAILURE. (September 2016) - Yamashita, Kaoru; Ichihara, Atsuhiro; Ito, Kentaro; Yoshida, Naohiro; Mitani, Fumiko; Endo, Jin; Sano, Motoaki; Fukuda, Keiichi; Morimoto, Satoshi
Abstract : Objective: Numerous clinical trials demonstrated that renin-angiotensin-aldosterone system (RAAS) was involved in the pathogenesis of hypertension-induced heart failure. While RAS is a major machinery required for aldosterone production, multiple minor systems, including catecholamine, could give rise to the aberrant aldosterone production beyond the RAS activation. We investigated the mechanism underlying the RAS-independent aldosterone production in heart failure. Design and Method: Dahl-salt sensitive rats fed high salt diet developed malignant hypertension, resulting in heart failure with inappropriately increased plasma aldosterone level. The gene expression pattern of the adrenal gland from heart failure rats showed strikingly upregulated b3-Adrenergic receptor (b3-AR) expression. Using Dahl-salt sensitive rats and H295R human adrenocortical carcinoma cells, we conducted immunohistochemical and molecular biological studies to assess whether b3-AR contribute to aldosterone production in heart failure. Results: Immunohistochemical staining confirmed that heart failure increased b3-AR expression in zona glomerulosa cells in adrenal gland of Dahl-salt sensitive rats. And the staining of pimonidazole, a hypoxia probe, revealed that the outer layer of adrenal cortex in the heart failure rat was under hypoxic condition. Hypoxia and DMOG, a chemical stabilizer of hypoxia-inducible factor, strongly induced b3-AR mRNA expression in H295R cells. Hypoxia-reoxygenation stimuli induced aldosterone production from H295R cells, which was blocked by SR59230A, a selective b3-AR antagonist, but not by losartan, an angiotensin II receptor blocker (ARB). Hypoxia endowed catecholamine responsiveness in H295R cells by increased b3-AR expression, wherein b3-AR agonist increased the phosphorylation levels of hormone-sensitive lipase (HSL) through activation of ERK pathway. Conclusions: In the present study, we demonstrated that the b3-AR induction in adrenal gland by hypoxia played an important role in aberrant aldosterone production in heart failure. The b3-AR-mediated catecholamine system could regulate the utilization of cholesterol, a substrate of aldosterone, via the ERK-HSL pathway.